Merjenje tlaka v vakuumski tehniki - Južnič, Stanislav (Vakuumist, 2000)
The article surveys the development of the measurement of pressures in three hundred years up to the middle of the 20th century. The data are given in chronological order, but on some occasions the development of each type of the manometer is described separately. Most manometers used in schools in lands inhibited by Slovenes are enumerated for each period.
Keywords: vakuumska tehnika; merjenje tlaka; manometri; zgodovinski pregledi